Temporal Dynamics of Cerebral Blood Flow, Cortical Damage, Apoptosis, Astrocyte–Vasculature Interaction and Astrogliosis in the Pericontusional Region after Traumatic Brain Injury - Villapol, Sonia; Byrnes, Kimberly R.; Symes, Aviva J. (Frontiers in Neurology, 2014)
Traumatic brain injury (TBI) results in a loss of brain tissue at the moment of impact in the cerebral cortex. Subsequent secondary injury involves the release of molecular signals with dramatic consequences for the integrity of damaged tissue, leading to the evolution of a pericontusional-damaged area minutes to days after in the initial injury. The mechanisms behind the progression of tissue loss remain under investigation. In this study, we analyzed the spatial-temporal profile of blood flow, apoptotic and astrocytic-vascular events in the cortical regions around the impact site at time points ranging from 5 hours to 2 months after TBI. We performed a mild-moderate controlled cortical impact injury in young adult mice and analyzed the glial and vascular response to injury. We observed a dramatic decrease in perilesional cerebral blood flow (CBF) immediately following the cortical impact that lasted until days later. CBF finally returned to baseline levels by 30 days post-injury (dpi). The initial impact also resulted in an immediate loss of tissue and cavity formation that gradually increased in size until 3 dpi. An increase in dying cells localized in the pericontusional region and a robust astrogliosis were also observed at 3 dpi. A strong vasculature interaction with astrocytes was established at 7 dpi. Glial scar formation began at 7 dpi and seemed to be compact by 60 dpi. Altogether, these results suggest that TBI results in a progression from acute neurodegeneration that precedes astrocytic activation, reformation of the neurovascular unit to glial scar formation. Understanding the multiple processes occurring after TBI is critical to the ability to develop neuroprotective therapeutics to ameliorate the short and long-term consequences of brain injury.